Science of Spices and Culinary Herbs - Latest Laboratory, Pre-Clinical, and Clinical Studies. - Atta-ur-Rahman; Choudhary, M. Iqbal; Yousuf, Sammer (Science of Spices and Culinary Herbs, 2019)
Many herbs and spices, in addition to their culinary use for taste, contain chemical compounds which have medicinal uses. For this reason, herbs and spies have been used for treating various ailments since ancient times. Modern scientific methods have enabled researchers to isolate bioactive compounds from herbs and spices and perform chemical analyses, which can be used to develop medicines to treat different diseases. This book series is a compilation of current reviews on studies performed on herbs and spices. Science of Spices and Culinary Herbs is essential reading for medicinal chemists,